Education and Learning Experiences of Language Assistants in Spain, 2019-2024 - Lagura, Andone; Macagba III, Samuel F (Universitas Ahmad Dahlan, 2025)
Background. Cultural exchange for teachers thrives when educators are supported by intentional professional growth opportunities, which is why this study explores how core professional development (PD) strategies shape the development of Filipino Language Assistants in Spain. Methods. This study employed a quantitative descriptive-correlational design to examine the personal growth and professional development of teachers participating in a cultural exchange program concerning their passion for teaching. The researchers developed instruments to measure PD strategies, personal growth, and teaching passion. A total of 83 Filipino Language Assistants (LAs) in Spain were selected through simple random sampling. The data was analyzed using both descriptive and inferential statistics.Results. Findings indicated that LAs recognized professional development, personal growth, and passion for teaching as evident in their participation in the program. No significant differences in these outcomes were found across age, gender, length of teaching experience, or program tenure. However, the PD strategies of mentoring, networking, collaborating, and reflecting emerged as key contributors to teachers’ professional growth and passion for teaching. Conclusion. The study underscores the importance of continuous professional development in sustaining teachers’ passion. Although PD may not be a primary component of the cultural exchange program, the Ministry of Education should consider integrating structured PD opportunities so that the program can be more successful. Embedding these four core strategies into future programming is essential for enhancing teacher growth, development, and long-term commitment to the teaching profession.